Strategic Financing Management in an Islamic Educational Institution: A SWOT-Based Case Study of Rumah Tahfidz Qur'an Al Harun - Marlina, Elvia Hani; Zakiyah, Sarah; Izzah, Ikfina Nurul; Rohim, Muhammad Syifa'ur; Ilahiya, Nabila Fadlla; Dian, Dian (Institut Agama Islam Negeri (IAIN) Curup, 2025)
This study aims to formulate financing management strategies in Islamic educational institutions, specifically at Rumah Tahfidz Qur'an Al-Harun, using a SWOT analysis approach. The analysis explores the strengths, weaknesses, opportunities, and threats in the institution's financing management. The findings indicate that the institution's dependency on family donors is a major weakness, while the loyalty of family donors represents a strength that needs to be maximized. The study also identifies significant opportunities to expand external networks and diversify funding sources, which can strengthen the institution's financial stability. The recommended strategies include diversifying funding sources, implementing technology-based budget management, and enhancing human resources capacity in financial management. By consistently applying the results of the SWOT analysis, Rumah Tahfidz Qur'an Al-Harun is expected to develop a sustainable and adaptive financing system in response to ongoing changes.